Extending The Shelf Life of Ready-To-Eat (RTE) Meat Product by Using Turmeric and Red Ginger as Film Coating of Active Packaging - Budi Dharma, Adi Sidharta (Diponegoro University, 2023)
The high demand for ready-to-eat (RTE) meat products is attributed to their convenience, safe, and healthy properties. The high nutritional content presence in the RTE meat product promotes the presence and growth of microbial pathogens such as Listeria monocytogenes, Escherichia coli, and Salmonella spp. It is considered to be the post-process contamination that is responsible for the shortening of a product’s shelf life which leads to spoilage or foodborne diseases. The aim of this systematic review is to develop and summarize the use of red ginger and turmeric bioactive compounds as antimicrobial materials to ensure their quality and extend the shelf-life of RTE beef rendang products. Thus, the current studies of coating technology of bioactive compounds and vacuum-sealed packaging are considered to be combined strategies that develop a more robust active packaging system. In order to gain a better understanding of this research field, a literature search was performed using the electronic databases Oxford Journals, Google Scholar, SAGE Journals, ScienceDirect, and Taylor & Francis which describes 26 primary studies. The findings state that the enhanced active packaging system by using bioactive compounds was associated with a significant prolongation of various RTE meat product’s shelf-life of up to 30 days of storage at room temperature. Moreover, the vacuum-sealed packaging in a retort pouch is also considered to improve the food safety environment against microbial contamination